Dampak Penggunaan Quick Response Code Indonsesian Standart (QRIS) Sebagai Solusi Pembayaran Digital pada Kegiatan dan Manajemen Keuangan Mahasiswa - Marisya Zahara; Tri Bunga Afani; Halimatus Sa'diyah; Salwa Juzika Fitri (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2025)
This study aims to analyze the impact of QRIS usage on students' transaction activities and financial management, particularly regarding ease of use, efficiency, and its influence on expenditure control and financial record-keeping. The study employs a descriptive quantitative approach with data collection techniques using an online questionnaire distributed via Google Forms. The sample consists of 45 students. Data was analyzed descriptively and presented in the form of percentages and graphs. The results of this study indicate that students are increasingly accustomed to making digital payments, in line with the fast-paced and digital lifestyle of the younger generation. However, this brings its own challenges, as students tend to be more consumptive and often make impulsive purchases when using QRIS compared to cash payments. This suggests that the effectiveness of QRIS in supporting financial management is highly dependent on individual discipline and financial literacy.